Polypharmacy Profile in Geriatric Patients - Syahrul Rifa'at; Armanto Makmun; Nesyana Nurmadilla; Kristian Liaury; Faisal Sommeng; Indah Lestari DK (Newinera Publisher, 2025)
Polypharmacy is a common phenomenon in geriatric patients and is strongly associated with aging and the presence of multiple comorbidities. In the elderly population, the simultaneous use of several medications increases the risk of negative outcomes, including higher healthcare costs, adverse drug reactions, drug–drug interactions, poor medication adherence, functional decline, and geriatric syndromes. Older adults are particularly prone to polypharmacy, which considerably heightens the risk of drug interactions, especially among those with multiple chronic conditions. The probability of drug–drug interactions escalates in direct proportion to the number of medications prescribed, as geriatric patients generally receive more prescriptions compared to younger populations. This study employed a Literature Review approach with a Narrative Review design. Polypharmacy is highly prevalent among geriatric patients and is significantly linked to disease burden, adverse effects, drug interactions, and increased treatment costs. Elderly patients with multiple comorbidities taking several medications concurrently are at heightened risk of harmful drug interactions, with the likelihood rising alongside the number of medications consumed. Geriatric patients are particularly vulnerable to polypharmacy, which substantially increases the risk of drug–drug interactions. The greater the number of medications prescribed, the higher the potential for adverse outcomes.